Imagens da Infância: Crianças, Aprendizagem e Formação nos Contos de Guimarães Rosa e Clarice Lispector - Ipiranga, Sarah Diva da Silva (2010)
For the analysis of children representations and the learning and educational processes in short stories by Guimarães Rosa and Clarice Lispector, it starts from the creation of a typology which systematizes and categorizes childhood images, their family, scholarship and society intermediations, as well as the relations established among individuals and groups who are built in the narratives: parents and children, students and teachers. The locals where the mediation takes place (nature, home and school) and the courses of learning and education which guide the establishment of childhood are also analyzed and articulated with various theoretical perspectives about the construction of childhood and the power injunctions which, in turn, are present in the confrontations and dialogues among these social actors. From an interdisciplinary perspective, the theoretical fields of Education, History and Literature intertwine in the authors’ thought about childhood and education: Norbert Elias, Philippe Ariès, Mikhail Bakhtin e Walter Benjamin. Besides that, in the establishment of childhood present in the selected short stories, the conceptual elements driving interference, which bounds the field of characters’ action, is observed: conflict, travel, sacrifice, language, imagination, humor, death and love. Thus, a place for reflections about the contributions of the literary text for pedagogical studies about children and their manners of being in the world is constructed with the thesis